2017
DOI: 10.1111/jace.14977
|View full text |Cite
|
Sign up to set email alerts
|

Spectral management and energy‐transfer mechanism of Eu3+‐doped β‐NaGdF4:Yb3+,Er3+ microcrystals

Abstract: b-NaGdF 4 :Yb 3+ ,Er 3+ upconversion (UC) microcrystals were prepared by a facile hydrothermal process with the assistance of ethylene diamine tertraacetic acid (EDTA). The b-NaGdF 4 UC microcrystal morphology was controlled by changing the doses of EDTA and NaF. Uniform hexagonal structure can be obtained at the 2 mmol EDTA and 9-10 mmol NaF. The UC emissions of b-NaGdF 4 :Yb 3+ , Er 3+ microcrystals were tuned by the variation of Eu 3+ doping level (0%-5%), where the red/green intensity ratio decreased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This indicated that Er 3+ ( 4 S 3/2 ) + Eu 3+ ( 7 F 0 ) -Er 3+ ( 4 I 15/2 ) + Eu 3+ ( 5 D 0 ) was the major energy depletion route in Yb 3+ /Er 3+ /Eu 3+ tri-doped microrods. 25 Similarly, in the Yb 3+ /Tm 3+ / Eu 3+ tri-doped samples, the lifetime of 475 nm wavelength declined from 705 to 580 ms as compared to that of NaYF 4 :Yb/Tm@NaTbF 4 :Eu microrods. This also verified the elimination of cross-relaxation of Tm-Eu pairs in the tip-modified microrods for high efficiency dual-mode luminescence.…”
Section: Resultsmentioning
confidence: 95%
“…This indicated that Er 3+ ( 4 S 3/2 ) + Eu 3+ ( 7 F 0 ) -Er 3+ ( 4 I 15/2 ) + Eu 3+ ( 5 D 0 ) was the major energy depletion route in Yb 3+ /Er 3+ /Eu 3+ tri-doped microrods. 25 Similarly, in the Yb 3+ /Tm 3+ / Eu 3+ tri-doped samples, the lifetime of 475 nm wavelength declined from 705 to 580 ms as compared to that of NaYF 4 :Yb/Tm@NaTbF 4 :Eu microrods. This also verified the elimination of cross-relaxation of Tm-Eu pairs in the tip-modified microrods for high efficiency dual-mode luminescence.…”
Section: Resultsmentioning
confidence: 95%